Development and Validation of a Problem-Based Learning E-Module Integrating Sidoarjo Milkfish Local Wisdom for Enhancing Students’ Critical Thinking Skills - Purwasih, Dewi; Dyah Hariani; Ulfi Faizah (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2026)
This study aims to evaluate the validity and readability of a Problem-Based Learning (PBL) e-module integrated with the local wisdom of milkfish cultivation in Sidoarjo on the topic of ecosystems to support the development of 10th-grade students’ critical thinking skills. The study employed the Fenrich development model, which comprises the stages of analysis, planning, design, development, and implementation, with each cycle involving evaluation and revision. The validity of the PBL e-module was assessed by three evaluators, comprising two expert lecturers and one biology teacher. Data were analyzed using descriptive quantitative and qualitative approaches. The results indicated that the PBL e-module achieved a validity score of 3.94, which was categorized as very valid. The Fry readability graph placed the text of the e-module at Grade 10, indicating that the e-module was appropriate for 10th-grade students. The findings indicate that the PBL e-module, integrated with local wisdom related to milkfish cultivation in Sidoarjo, is valid and appropriate for biology learning. Integrating local wisdom and contextual issues into biology education has the potential to support the development of students’ critical thinking skills.